2001
DOI: 10.1177/096973300100800106
|View full text |Cite
|
Sign up to set email alerts
|

The Teaching of Health Care Ethics to Students of Nursing in the UK: a pilot study

Abstract: Senior lecturers/lecturers in mental health nursing (11 in round one, nine in round two, and eight in the final round) participated in a three-round Delphi study into the teaching of health care ethics (HCE) to students of nursing. The participants were drawn from six (round one) and four (round three) UK universities. Information was gathered on the organization, methods used and content of HCE modules. Questionnaire responses were transcribed and the content analysed for patterns of interest and areas of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 16 publications
0
42
0
Order By: Relevance
“…We attempted to resolve this bias by using 2 reviewers to abstract the articles and applying only Beauchamp and Childress' principle-based approach to bioethics, which served as a classification system in order to analyze retrieved literature and help curb reviewer biases. We chose Beauchamp and Childress framework because it is the most widely adopted and taught scheme in medical ethics across healthcare disciplines in the United States (36-38). Although we selected the ethical framework most familiar to healthcare providers, we acknowledge that this may have slightly limited our methodology and that an alternative classification system would have revealed a different distribution of ethical content in the plastic surgical literature.…”
Section: Discussionmentioning
confidence: 99%
“…We attempted to resolve this bias by using 2 reviewers to abstract the articles and applying only Beauchamp and Childress' principle-based approach to bioethics, which served as a classification system in order to analyze retrieved literature and help curb reviewer biases. We chose Beauchamp and Childress framework because it is the most widely adopted and taught scheme in medical ethics across healthcare disciplines in the United States (36-38). Although we selected the ethical framework most familiar to healthcare providers, we acknowledge that this may have slightly limited our methodology and that an alternative classification system would have revealed a different distribution of ethical content in the plastic surgical literature.…”
Section: Discussionmentioning
confidence: 99%
“…Methods for teaching and learning ethics reported in the literature include modules that focus on deontology and consequentialism in nursing [12], using artistic expression to promote awareness of personal values and beliefs in occupational therapy [13], embedding ethics into interprofessional education [14,15], using vignettes [16] and scenarios with nursing students in online and face-to-face environments [17], as well as using ambiguous cases with ethical dilemmas in physiotherapy [8]. A textual evaluation of course descriptions in occupational therapy and physiotherapy programs in Canada found that programs met the professional standards for expectations of ethics curriculum but did not address the actual learning outcomes for students [18].…”
Section: Introductionmentioning
confidence: 99%
“…Opportunities for practising ethical decision making often constitute part of the 'hidden curriculum' [11] and are rarely given enough attention [12]. In addition, outcomes of curricula which focus on the teaching of ethics are difficult to extract as they may relate to personal and professional craft knowledge, rather than clearly identifiable and measurable propositional knowledge [19].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, family, community or the greater self always carry a greater weight in Asian value systems than individuals. Since the re-emphasis of the importance of bioethics in the twentieth century took place in the West, 1 Asian people have the impression that bioethics is a Western product. For instance, when discussing the theoretical foundations of bioethics, we refer to John Mill's utilitarianism and Kant's deontologism.…”
Section: Introductionmentioning
confidence: 99%